Rethinking Sustainability Monitoring in the Arctic by Linking Resilience and Sustainable Development in Socially-Oriented Observations: A Perspective - Tatiana Vlasova; Andrey N. Petrov; Sergey Volkov (Sustainability, 2020)
Monitoring of social-ecological systems dynamics and sustainability is of high importance in a rapidly changing Arctic. The goal of this essay is to discuss and articulate the principles for designing a suitable Arctic sustainability monitoring framework based on the convergence between resilience thinking and sustainable development paradigms. We propose to integrate sustainability monitoring into the socially-oriented observations (SOO) methodologies in order to design Arctic sustainability monitoring as a transdisciplinary participatory activity that results in both co-production of sustainability knowledge and building more sustainable and resilient Arctic social-ecological systems by enabling continuous observation and informed decision-making. Special attention is given to approaches for developing sustainability indicators to monitor trends in Arctic social-ecological systems. It is argued that sustainability monitoring is a valuable component of the Arctic sustainability knowledge system that integrates social and natural sciences and engages Indigenous, local, and traditional knowledge, entrepreneurship, education, and decision-making. Bringing together diverse knowledge systems is the primary route to collectively pursue sustainability in a holistic, polycentric, multifaceted, participatory, and knowledge-driven manner. Transdisciplinary SOO approaches and methods are specifically discussed.